Variação dos elementos xilemáticos ao longo do caule de Parkia ulei (Harns) Kuhlma - Leguminosae Mimosoideae - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2002)
The little knowledge about anatomical variation in tropical species has led researchers to develop studies to better understand the causes of this variation. The present study aims to analyze the variations in the anatomical structures of the axial and radial wood of P. ulei, aiming to better characterize the anatomy of the species. To this end, wood discs were obtained along the stem, from which test bodies were obtained in the medulla-exchange direction. To measure the length, wall thickness and width of the fiber lumen, slides containing wood macerate were made. The axial direction showed an increase in fiber length and lumen width from the base towards the middle. The wall thickness showed stable values up to 11.30 meters, followed by a small increase towards the apex. In the radial direction, the lowest values in fiber length were observed near the pith, showing an increase and stabilizing towards the cambium. The width of the lumen showed a marked reduction tending to stabilize near the cambium. The wall thickness showed an increase in the direction from pith to cambium and a subsequent tendency to stabilize. The results agree with those found by Urbinati (2002) for T. ivorensis. Probably, the anatomical characteristic observed for fibers in P. ulei is due to the distinct presence of juvenile and adult wood in the studied species.
Variation of xylematic elements along the stem of Parkia ulei (Harns) Kuhlma - Leguminosae Mimosoideae
Keywords: Parkia ulei (Harns) Kuhlma; Leguminosae Mimosoideae; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL::ANATOMIA VEGETAL